Applying argumentation in primary pre-service teacher education – a teaching-learning sequence using collaborative video annotations - Hierrezuelo-Osorio, José Manuel; García-Ruiz, María Cristina; Lupión-Cobos, Teresa (My University, 2019)
Argumentation process not only helps to promote the construction of new knowledge but also gives the students the possibility of participating in socio-scientific debates, approaching real science to the scholar environment. As related argumentation skills are therefore fundamental for the professional profile of science educators, in this communication, we would like to introduce a short sequence addressed to improve the argumentative competence in primary pre-service students through the use of collaborative video annotations. In a subsequent analysis, comparisons of the pre/post-test profiles together with the productions of the students will provide a complete view of the degree of argumentation at this educational level and the improvements that should be implemented
Keywords: Pensamiento crítico; Argumentación; Pensamiento crítico; Prácticas científicas